KRITERIA PROPOSAL PERDAMAIAN PKPU YANG CUKUP TERJAMIN DALAM KASUS KSP INDOSURYA CIPTA - Liony Gracia Christiani Purba; Sri Bakti Yunari (Reformasi Hukum Trisakti, 2022)
A positive development in the PKPU process should be the ratification of the Peace Plan (Homologation). The implementation of payments in the instance of KSP Indosurya, however, did not follow the terms of the homologation agreement. The key issue with this piece is how the creditors of KSP Indosurya attempt to determine whether a peace plan falls under the category of suitably assured. The study method employed is normative legal research, with literature reviews based on secondary data and primary data from interviews supporting it. This study's methodology involves making inferences through deductive reasoning and performing descriptive analyses. The analyses' findings show that KSP Indosurya's peace proposal lacks adequate guarantees. The truth is that the peace proposal offered by KSP Indosurya is not sufficiently guaranteed and the implementation is not according to what was mutually agreed upon. Indosurya Cipta KSP creditors in assessing a peace proposal can submit an examination of the cooperative's financial statements by an independent expert in accordance with Article 238 of the Bankruptcy Law and PKPU.